RFID and Voice Recognition Based Dual Security System: A Robust Secured Control to Access Through Door Lock Operation: - - Nasution, Torkis; Herwin; Andesa, Khusaeri (Journal of Research and Technology, 2024)
Describe the problem faced in the research. Explain the method used in the research. Give the result of the research. Abstract contains of maximum 200 words Security system solutions for strategically important facilities are put in place to prevent unauthorized access. There are numerous automated access control systems available, but they are relatively expensive and difficult to use. The goal of this research is to create a security system that combines voice recognition and Radio Frequency Identification (RFID) to reduce costs while providing optimal security. This system is based on the Raspberry PI, and it uses RFID reading to scan and identify the user, as well as voice recognition to grant entry by opening the door. The microcontroller also provides access via a visual display in the form of a liquid crystal display for easy identification of the server room access control. Identity information and voice recognition are saved in a database, which can be accessed at any time. The RFID reader can scan a tag within 20 cm in two seconds and perform voice recognition in one second. The data is stored in the database after the two types of access control are identified and recognized. To open the door, the motor will move. This system is designed for ten users and has a 1% error rate